2007
DOI: 10.1002/ardp.200700080
|View full text |Cite
|
Sign up to set email alerts
|

Rifalazil and Other Benzoxazinorifamycins in the Treatment of Chlamydia‐Based Persistent Infections

Abstract: Rifalazil is a benzoxazinorifamycin which inhibits bacterial DNA-dependent RNA polymerase. The benzoxazine ring endows benzoxazinorifamycins with unique physical and chemical characteristics which favor the use of rifalazil and derivatives in treating diseases caused by the obligate intracellular pathogens of the genus chlamydia. Minimal inhibitory concentrations of benzoxazinorifamycins against chlamydia are in the pg/mL range. These compounds have potential as monotherapeutic agents to treat chlamydia-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 100 publications
1
10
0
Order By: Relevance
“…Rifalazil plasma concentrations were detectable after more than 3 weeks in all subjects after a single 25-mg dose of rifalazil, as expected based on rifalazil's previously reported long elimination half-life of ϳ100 h (11). Treatment failures at visit 2 (day 8 to 12) tended to have lower rifalazil plasma concentrations than those diagnosed as cured at the same visit; however, the difference was not significant.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Rifalazil plasma concentrations were detectable after more than 3 weeks in all subjects after a single 25-mg dose of rifalazil, as expected based on rifalazil's previously reported long elimination half-life of ϳ100 h (11). Treatment failures at visit 2 (day 8 to 12) tended to have lower rifalazil plasma concentrations than those diagnosed as cured at the same visit; however, the difference was not significant.…”
Section: Discussionsupporting
confidence: 74%
“…In vitro studies have shown that rifalazil has a significantly greater antimicrobial potency against C. trachomatis than azithromycin, with their MIC 90 s being 0.00025 and 0.125 g/ml, respectively (11)(12)(13). Rifalazil has a long elimination half-life of approximately 100 h and achieves high intracellular concentrations (11), which could reduce the likelihood of treatment failure and lessen the incidence of repeat infections. The clinical benefit of a single oral dose of 25 mg of rifalazil in treating C. trachomatis was demonstrated in a phase II clinical study which enrolled men with nongonococcal urethritis (NGU) (14).…”
mentioning
confidence: 99%
“…At present, RIF continues to be a first-line drug for the treatment of tuberculosis (5). Through the years additional derivatives have been developed to treat a wider range of bacterial infections (3); for example, rifalazil serves as an effective antibiotic against Chlamydia-based persistent infections (6), and rifaximin is used to treat travelers' diarrhea and irritable bowel syndrome (7,8).…”
mentioning
confidence: 99%
“…6 Because vascular infection with C pneumoniae is likely to require prolonged courses of therapy, the ability of rifalazil to promote long-term eradication of infection may be beneficial in the treatment of patients with PAD. 7 Accordingly, the goal of this study was to determine whether rifalazil would be effective in patients with symptomatic PAD. The Prospective Evaluation of Rifalazil Effect on Vascular Symptoms of Intermittent Claudication and Other Endpoints in Chlamydia pneumoniae Seropositive Patients (PROVIDENCE-1) study was designed to test the hypothesis that this potent anti-Chlamydial agent would improve peak walking time (PWT) relative to placebo in PAD patients with intermittent claudication.…”
Section: Clinical Perspective P 458mentioning
confidence: 99%